Math Problems

## Questions

 $$y = x^2 + 8 x + 15$$ $$y = 4 x^2 + 8 x$$ $$y = x^2 -3 x -4$$ $$y = 2 x^2 -2 x -4$$ $$y = 2 x^2 + 3 x -9$$ $$y = 4 x^2 + 6 x + 2$$ $$y = 3 x^2 + x -2$$ $$y = x^2 -7 x + 10$$ $$y = 4 x^2 + 5 x -6$$ $$y = x^2 + 2 x -8$$ $$y = x^2 -2 x -3$$ $$y = x^2 + 12 x + 36$$ $$y = 2 x^2 + 6 x + 4$$ $$y = x^2 + 6 x + 8$$ $$y = x^2 + 7 x + 12$$ $$y = x^2 -8 x + 15$$ $$y = x^2 + 4 x -5$$ $$y = x^2 + x -12$$ $$y = x^2 + 10 x + 24$$ $$y = 4 x^2 + 7 x + 3$$ $$y = 4 x^2 -12 x$$ $$y = x^2 -x -6$$ $$y = 4 x^2 + 7 x -2$$ $$y = 3 x^2 + 9 x + 6$$ $$y = 2 x^2 -x -1$$ $$y = 2 x^2 -4 x$$ $$y = x^2 -3 x$$ $$y = x^2 + 2 x + 1$$

 $$y = x^2 + 8 x + 15$$ ⇒ $$(x + 5)(x + 3)$$ $$y = 4 x^2 + 8 x$$ ⇒ $$4(x)(x + 2)$$ $$y = x^2 -3 x -4$$ ⇒ $$(x -4)(x + 1)$$ $$y = 2 x^2 -2 x -4$$ ⇒ $$2(x + 1)(x -2)$$ $$y = 2 x^2 + 3 x -9$$ ⇒ $$(2 x -3)(x + 3)$$ $$y = 4 x^2 + 6 x + 2$$ ⇒ $$2(2 x + 1)(x + 1)$$ $$y = 3 x^2 + x -2$$ ⇒ $$(3 x -2)(x + 1)$$ $$y = x^2 -7 x + 10$$ ⇒ $$(x -2)(x -5)$$ $$y = 4 x^2 + 5 x -6$$ ⇒ $$(4 x -3)(x + 2)$$ $$y = x^2 + 2 x -8$$ ⇒ $$(x + 4)(x -2)$$ $$y = x^2 -2 x -3$$ ⇒ $$(x + 1)(x -3)$$ $$y = x^2 + 12 x + 36$$ ⇒ $$(x + 6)(x + 6)$$ $$y = 2 x^2 + 6 x + 4$$ ⇒ $$2(x + 1)(x + 2)$$ $$y = x^2 + 6 x + 8$$ ⇒ $$(x + 4)(x + 2)$$ $$y = x^2 + 7 x + 12$$ ⇒ $$(x + 4)(x + 3)$$ $$y = x^2 -8 x + 15$$ ⇒ $$(x -5)(x -3)$$ $$y = x^2 + 4 x -5$$ ⇒ $$(x -1)(x + 5)$$ $$y = x^2 + x -12$$ ⇒ $$(x + 4)(x -3)$$ $$y = x^2 + 10 x + 24$$ ⇒ $$(x + 6)(x + 4)$$ $$y = 4 x^2 + 7 x + 3$$ ⇒ $$(4 x + 3)(x + 1)$$ $$y = 4 x^2 -12 x$$ ⇒ $$4(x)(x -3)$$ $$y = x^2 -x -6$$ ⇒ $$(x -3)(x + 2)$$ $$y = 4 x^2 + 7 x -2$$ ⇒ $$(4 x -1)(x + 2)$$ $$y = 3 x^2 + 9 x + 6$$ ⇒ $$3(x + 1)(x + 2)$$ $$y = 2 x^2 -x -1$$ ⇒ $$(2 x + 1)(x -1)$$ $$y = 2 x^2 -4 x$$ ⇒ $$2(x)(x -2)$$ $$y = x^2 -3 x$$ ⇒ $$(x -3)(x)$$ $$y = x^2 + 2 x + 1$$ ⇒ $$(x + 1)(x + 1)$$